Comparison between the multi-shaft and the single-shaft combined cycle power plants - Chaitrak, Kanticha; Paoprasert, Naraphorn; Anussornnitisarn, Pornthep (International Journal of Power Electronics and Drive Systems (IJPEDS), 2023)
A multi-shaft system has been adopted by power plants in Thailand for decades; however, for newer units, single-shaft systems have become more popular. This paper compared reliability measures—the system means failure rate, system mean repair rate, and system unavailability indices—between multi-shaft and single-shaft combined cycle power plants (CCPPs). The results showed that the long-term system availability of one multi-shaft CCPP was higher than each of the single-shaft units by 40.70%. In addition, the multi-shaft unit had a 42.14% longer mean time to failure (MTTF) than the single-shaft unit. Finally, the multi-shaft CCPP had 34.59% higher expected capacity than that of the single-shaft system.